Bersinergi Untuk Padukuhan Sorowajan: Kuliah Kerja Nyata Universitas Cokroaminoto Yogyakarta 2025 - Kurniawan, Muhammad Jefri (Universitas Cokroaminoto Yogyakarta, 2026)
Community Service (KKN) is an academic program that aims to integrate community service activities into the higher education system. KKN UCY 2025 in Padukuhan Sorowajan was implemented with a participatory approach and qualitative methods, including observation, interviews, and implementation of educational, social, economic, and cultural-based programs. The activities carried out included tutoring, religious teaching, creative economic skills training, socialization of laws related to illegal online loans, healthy exercise, and cultural preservation through ruwahan events. The results of the activities showed an increase in public awareness in the fields of education, economics, and law, as well as strengthening local traditions. The success of this program was supported by the synergy between students, village officials, and the community in creating sustainable solutions.